2008
DOI: 10.1099/vir.0.83624-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acids of the beet necrotic yellow vein virus p25 protein required for induction of the resistance response in leaves of Beta vulgaris plants

Abstract: The RNA3-encoded p25 protein of beet necrotic yellow vein virus (BNYVV) is responsible for the production of rhizomania symptoms of sugar beet roots (Beta vulgaris subsp. vulgaris). Here, it was found that the presence of the p25 protein is also associated with the resistance response in rub-inoculated leaves of sugar beet and wild beet (Beta vulgaris subsp. maritima) plants. The resistance phenotype displayed a range of symptoms from no visible lesions to necrotic or greyish lesions at the inoculation site, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 45 publications
1
42
0
1
Order By: Relevance
“…P25 represents the viral pathogenicity factor responsible for the development of root beard-like symptoms and yield reduction (Koenig et al 1991) and possesses highly variable amino acid motifs . Additionally, phenotypic local lesions on mechanically-inoculated sugar beet leaves are dependent on P25 composition, and vary greatly between different BNYVV isolates and resistance sources (Tamada et al 1989;Chiba et al 2008). Therefore, mutations in P25 are plausible candidates responsible for increased BNYVV pathogenicity, though experimental evidence is lacking.…”
Section: Resistance Test With Adjusted Inoculummentioning
confidence: 97%
See 1 more Smart Citation
“…P25 represents the viral pathogenicity factor responsible for the development of root beard-like symptoms and yield reduction (Koenig et al 1991) and possesses highly variable amino acid motifs . Additionally, phenotypic local lesions on mechanically-inoculated sugar beet leaves are dependent on P25 composition, and vary greatly between different BNYVV isolates and resistance sources (Tamada et al 1989;Chiba et al 2008). Therefore, mutations in P25 are plausible candidates responsible for increased BNYVV pathogenicity, though experimental evidence is lacking.…”
Section: Resistance Test With Adjusted Inoculummentioning
confidence: 97%
“…However, it is still unclear how the resistance-breaking abilities in these soils arise. There is a growing body of evidence that genetic changes in the RNA 3 encoded viral pathogenicity factor P25 are associated with BNYVV ability to overcome plant resistance (Acosta-Leal and Rush 2007;Chiba et al 2008), though final experimental proof applying field isolates is still lacking. On the other hand, although using an artificial experimental system with zoospore cultures and hydroponics, Scholten et al (1994) found evidence for the involvement of enhanced vector concentration and/or secondary multiplication, and that possible increased BNYVV transmission was involved in the resistance-breaking phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Klein et al (2007) studied the influence of P25 sequence variation on its oligomerization and pathogenicity for Tetragonia expansa leaves. Chiba et al (2008) investigated the influence of mutations in the P25 aa 68, 69 and 70 on the local lesion response in mechanically inoculated leaves of lines of Beta maritima and of the sugar beet varieties Rizor and Monomidori. Acosta- Leal & Rush (2007) studied the P25 amino acid composition in fieldgrown Rz1 resistance gene-containing sugar beet which did or did not show resistance-breaking.…”
mentioning
confidence: 99%
“…In position 68 these authors detected either a 'C' or an 'L' which did not correlate with resistance-breaking. The amino acid in position 68 can, however, influence the type of local lesions formed in beet leaves (Chiba et al, 2008). It remains to be shown whether the 'E' in position 135 found by Acosta-Leal & Rush (2007) in plants showing resistancebreaking also contributes to an increased virus accumulation in beet roots.…”
mentioning
confidence: 99%
“…Consequently, it is generally assumed that the avirulence factor is not the nucleic acid by itself but the protein it encodes. Convincing evidence has been produced for this (Moury et al 2004;Schirmer et al 2005;Charron et al 2008;Chiba et al 2008), although non-coding regions of the virus genome have been shown to be the avirulence factor for at least two resistances (Díaz et al 2004;Szittya and Burgyan 2001). In theory, when nucleotide substitutions at different positions in the viral genome are required for virulence, recombination or reassortment between two (or more) avirulent virus isolates could also generate a novel virulent strain.…”
Section: Resistance Durabilitymentioning
confidence: 94%